Formulation and Evaluation of Anti-Dandruff Hair Mask from Lime Peel Extract (Citrus aurantifolia): Antibacterial Activity, Stability, and Safety Assessment - Andini Putri Maharani; Eriska Agustin; Dani Prasetyo (Asosiasi Dosen Muda Indonesia, 2026)
Dandruff is a common scalp condition caused by Staphylococcus aureus, leading to itching, irritation, and reduced self-confidence. Natural alternatives, such as lime peel (Citrus aurantifolia), which contains antibacterial compounds like flavonoids and saponins, show potential as an effective anti-dandruff agent. Objective: This study aimed to formulate a hair mask using lime peel extract as an anti-dandruff agent and evaluate its physical quality, safety, and antibacterial activity. Methods: A quantitative experimental approach was used, preparing three formulations with 5%, 10%, and 15% lime peel extract. Evaluations included organoleptic, homogeneity, pH, spreadability, stability, irritation, and antibacterial activity tests against Staphylococcus aureus. Results: Formulations F0, F1, and F2 remained stable for 28 days, while F3 showed phase separation from days 21 to 28. All formulations had pH values within the safe range (4.5–6.5). Spreadability was acceptable, and irritation tests revealed that only F3 caused irritation. F3 showed the largest inhibition zone in antibacterial tests, indicating the highest antibacterial efficacy. Implications: This study suggests that higher concentrations of lime peel extract enhance antibacterial efficacy but may compromise stability and cause irritation. Further optimization is needed to improve safety and stability while maintaining effectiveness. Originality: This research contributes original insights into the use of lime peel extract for anti-dandruff treatments, offering a natural alternative to synthetic agents. The study provides valuable data for developing safer and more effective cosmetic formulations.